Verificação experimental de vibrações paramétricas em vigas - Simão, Reny (1974)
Experimental investigation of parametric resonance of a bar subjected to an axial compressive force P, smaller than the buckling load and to an oscillating torque of the type T = T₀ + T₁1 cos Ω t, , where T₀, T₁ e Ω are independent pameters. The regions of elastodynamic instability are determined experimentally for a bar fixed in flexure at both ends and fixed-free in torsion, for various values of the axial compression. The results are compared with those of an existing theory.